Congenital circumscribed basaloid follicular hamartoma. - Ingravallo, G. (European Journal of Pediatric Dermatology, 2020)
Basaloid follicular hamartoma is characterized by well-defined pathological findings, consisting of strands of basaloid cells connected with the hair follicles and immersed in a concentric loose stroma. It differs from basal cell carcinoma for the absence of clefts between the neoformation and the stroma and for the lack of mitosis and nuclear atypia (2). On the other hand, the clinical features are extremely variable going from generalized forms with autosomal dominant transmission, often associated with skeletal malformations, to nevoid forms distributed along the lines of Blaschko, to congenital, as in our case, or acquired circumscribed lesions. The individual lesions have no clinical characteristics (1), as they may be papules, nodules, plaques or dyschromic lesions, so the diagnosis often comes from the histological examination.